Workplace innovations in the Republic of Ireland - McCartney, John; Teague, Paul (Economic & Social Studies, 1997)
Many explanations have emerged for Ireland's dramatic economic recovery, but virtually all have taken a macroeconomic perspective. This paper enriches our understanding of recent progress by presenting original survey data on establishment-level work organisation and human resource innovations. The survey indicates that most Irish establishments are actively reorganising work arrangements. There is also strong evidence to show that they are supporting these developments with complementary human resource management innovations. A key driving force behind these changes appears to be economic openness; high exporters and branches of multinational corporations are more innovative. So too are establishments adopting high value added corporate strategies. Under certain circumstances, however, unionisation is negatively associated with work systems innovation.
Keywords: Innovation; Working conditions; Ireland; Work organisation